Cell-Specific Effects of GATA (GATA Zinc Finger Transcription Factor Family)-6 in Vascular Smooth Muscle and Endothelial Cells on Vascular Injury Neointimal Formation. Issue 5 (May 2019) - Zhuang, Tao; Liu, Jie; Chen, Xiaoli; Pi, Jingjiang; Kuang, Yashu; Wang, Yanfang; Tomlinson, Brain; Chan, Paul; Zhang, Qi; Li, Ying; Yu, Zuoren; Zheng, Xiangjian; et al.
Abstract : Objective—: Transcription factor GATA (GATA zinc finger transcription factor family)-6 is highly expressed in vessels and rapidly downregulated in balloon-injured carotid arteries and viral delivery of GATA-6 to the vessels limited the neointimal formation, however, little is known about its cell-specific regulation of in vivo vascular smooth muscle cell (VSMC) phenotypic state contributing to neointimal formation. This study aims to determine the role of vascular cell-specific GATA-6 in ligation- or injury-induced neointimal hyperplasia in vivo. Approach and Results—: Endothelial cell and VSMC-specific GATA-6 deletion mice are generated, and the results indicate that endothelial cell-specific GATA-6 deletion mice exhibit significant decrease of VSMC proliferation and attenuation of neointimal formation after artery ligation and injury compared with the wild-type littermate control mice. PDGF (platelet-derived growth factor)-B is identified as a direct target gene, and endothelial cell-GATA-6-PDGF-B pathway regulates VSMC proliferation and migration in a paracrine manner which controls the neointimal formation. In contrast, VSMC-specific GATA-6 deletion promotes injury-induced VSMC transformation from contractile to proliferative synthetic phenotype leading to increased neointimal formation. CCN (cysteine-rich 61/connective tissue growth factor/nephroblastoma overexpressed family)-5 is identified as a novel target gene, and VSMC-specific CCN-5 overexpression in mice reverses the VSMC-GATA-6 deletion-mediated increased cell proliferation and migration and finally attenuates the neointimal formation. Conclusions—: This study gives us a direct in vivo evidence of GATA-6 cell lineage-specific regulation of PDGF-B and CCN-5 on VSMC phenotypic state, proliferation and migration contributing to neointimal formation, which advances our understanding of in vivo neointimal hyperplasia, meanwhile also provides opportunities for future therapeutic interventions. Abstract : Supplemental Digital Content is available in the text.